Acute Phase Reactants and Hematologic Profiles vs Blood Culture in Late Preterm Neonatal Sepsis - Naji, Aiub Bassim; Hadi, Ammer Muhssin; Muhssin, Akram Hamdi; Alkhateeb, Dheyaa Aldeen (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Neonatal sepsis involves physical and laboratory findings due to infection within the first 30 days of life, with preterm infants being six times more at risk than term infants due to their immature immune systems and prolonged hospitalization. Sepsis is more common in males and in developing countries. The World Health Organization estimates 5 million neonatal deaths annually, mostly in developing countries. Despite advances in neonatal care, late-onset sepsis remains a significant cause of morbidity and mortality. Aim: To evaluate the significance of acute phase reactants and hematological findings versus blood culture in diagnosing sepsis in late preterm infants. Method: A cross-sectional study of 70 neonates with suspected sepsis from January 2011 to March 2012 at Babylon Teaching Hospital. Patients were classified as having early or late-onset neonatal sepsis. Tests included blood culture, c-reactive protein, erythrocyte sedimentation rate, white blood cell, platelets, and band cells. Results: Of the 70 patients, 55.7% were male and 44.3% were female. Early sepsis was observed in 40% of patients, and late sepsis in 60%. Blood culture was positive in 25.7% of cases, with 83.3% of these in early sepsis. CRP was positive in 91.4% of patients, including 100% of early sepsis cases and 85.7% of late sepsis cases. Positive band cells were found in 45.7% of cases, with 83.3% of these having positive blood cultures. Abnormal WBC counts (<5000 or >21000) were found in 64.3% of cases. Low platelet counts (<150,000) were observed in 55.7% of patients, with 67.8% in early sepsis and 47.6% in late sepsis. Elevated ESR (>6mm/h) was seen in 91.4% of cases. Conclusion: Blood culture remains the gold standard for diagnosing sepsis, though its accuracy can be affected by antibiotic use. Combining multiple diagnostic tests improves predictive values over single tests. Highlights: Late-onset sepsis remains a major cause of neonatal morbidity and mortality. CRP and ESR showed high positivity, supporting their value in early detection. Blood culture is essential but benefits from combined diagnostic markers. Keywords: Late Preterm Infant, Neonatal Sepsis, Blood Culture, Infant, CRP.